Fast Production of Diacylglycerol in a Solvent Free System via Lipase Catalyzed Esterification Using a Bubble Column Reactor. (23rd February 2016) - Liu, Manman; Fu, Junning; Teng, Yinglai; Zhang, Zhen; Zhang, Ning; Wang, Yong
Abstract: In this study, diacylglycerols (DAG) were synthesized rapidly (~30 min) in a solvent‐free system via esterification of glycerol with fatty acids (FA, the mixture of 60 wt% palm oil deodorizer distillate and 40 wt% oleic acid) catalyzed by Lipozyme 435 (Novozymes A/S, Copenhagen, Denmark) using a bubble column reactor. The content of DAG, monoacylglycerols (MAG), triacylglycerols (TAG) and free fatty acids (FFA) in the crude product were 57.94 ± 1.60 wt%, 24.68 ± 2.08 wt%, 2.67 ± 1.72 wt% and 14.69 ± 1.22 wt%, respectively under the selected conditions, which were enzyme load of 5.0 wt%, glycerol/FA mole ratio of 7.5, initial water content of 2.5 wt%, reaction temperature of 60 °C, reaction time of 30 min and N2 gas flow of 10.6 cm min −1 . The final product containing 91.30 ± 1.10 wt% of DAG was obtained by one‐step molecular distillation at 200 °C. The reusability of Lipozyme 435 was investigated by evaluating the esterification degree (ED) and the DAG content in the crude products in 30 successive runs. The enzyme retained 95.10 % of its original activity during 30 successive runs according to comparison of the ED. The new process showed a very high efficiency in production of DAG with a high purity. The ratio of positional isomers 1, 3‐DAG to 1, 2 ‐DAG was 2:1 in the final product. The certain plasticity (melting point of 44 °C) and content of unsaturated fatty acids made the product a valuable food ingredient.